Digital Authority and the Reification of Polygamy: A Framing Analysis of Salafi Discourse on Indonesian Social Media - Farichatul Fauziyah; Cecep Soleh Kurniawan (Journal of Digital Islamic Thought, 2026)
The digitalization of Islamic proselytization (da’wah) has fundamentally reconfigured religious authority, particularly regarding contemporary discourses on polygamy on social media. This study utilizes Robert Entman’s framing framework to interrogate the conceptualization of polygamy within the digital homiletics of the Instagram account @khalidbasalamahofficial. Findings suggest that the selective appropriation of hadith reifies polygamy as an immutable divine law, effectively marginalizing ethical imperatives such as gender justice, reciprocity, and female well-being. Under this digital framework, polygamy is synthesized as a manifestation of male piety rather than a relational practice grounded in equality and moral accountability. In response, this study leverages the qirā’ah mubādalah (reciprocal reading) approach to propose an alternative hermeneutic that prioritizes justice, mutualism, and public interest (mas}lah}ah) as the teleological cores of Islamic jurisprudence. By synthesizing framing analysis with mubādalah-based interpretation, this research elucidates the ideological underpinnings of digital discourse and emphasizes the urgency of advancing gender-just human-centered interpretations of Islam in the digital sphere.